Neodymium-iron-boron magnet and preparation method and application thereof

Through incomplete dehydrogenation process and multi-stage sintering process, combined with the coating process, the problem of introducing impurity elements in the preparation of neodymium iron boron magnets is solved, and the coercive force and performance stability of the magnet are improved.

CN119495506APending Publication Date: 2025-02-21NINGBO KONIT IND +4
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411793644.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the process of preparing the sintered NdFeB magnet, the chemical properties of NdFeB magnetic powder are active and have poor fluidity, resulting in the need to add organic additives such as antioxidants, lubricants and other organic additives and nitrogen, and introduce impurity elements such as carbon, nitrogen and oxygen to reduce the magnet's Coercive force.

Method used

The incomplete dehydrogenation process is used to control the hydrogen content in the magnet, reduce the free energy of the grain boundary phase, avoid the combination of impurity elements with rare earth-rich, and cooperate with the multi-stage sintering process and coating process to protect the magnet and avoid impurities adsorption.

Benefits of technology

Effectively reduce the content of impurity elements in the magnet, avoid deterioration of the magnetic properties of impurity elements, avoid cracks in the magnet during sintering, and prevent impurities from adsorbing during subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178314710000121
    Figure BDA0005178314710000121
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron magnet and a preparation method and application thereof, and the preparation method comprises the following steps: preparing a neodymium-iron-boron melt-spun sheet from a magnet raw material, and then carrying out hydrogen demolishing treatment on the neodymium-iron-boron melt-spun sheet to obtain coarse powder; the hydrogen decrepitation treatment comprises a hydrogen absorption step and a dehydrogenation step which are carried out in sequence, and the dehydrogenation temperature is 250-350 DEG C; coating the coarse powder with an organic additive to obtain a coating material; and carrying out grinding, molding, sintering treatment and aging treatment on the coating material to obtain the neodymium-iron-boron magnet. According to the preparation method, the content of hydrogen in the coarse powder is controlled through an incomplete dehydrogenation process, so that the content of impurity elements in the magnet is reduced, degradation of the impurity elements on the magnetic performance is avoided, meanwhile, the problem that cracks are formed in the magnet in the sintering process due to the incomplete dehydrogenation process is avoided in cooperation with a multi-stage sintering process, and the quality of the magnet is improved. And a coating process is matched to protect the magnet, so that the problem that the magnet adsorbs impurities again in a subsequent treatment process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of neodymium iron boron magnets and relates to a neodymium iron boron magnet and a preparation method and application thereof. Background Art

[0002] Sintered NdFeB magnets are widely used in many fields such as automotive industry, electronic communications, clean energy, industrial robots, and aerospace due to their excellent magnetic properties. As the demand for them continues to expand, the requirements for magnet properties, such as remanence and coercive force, are also getting higher and higher.

[0003] At present, in the process of preparing sintered NdFeB magnets, due to the active chemical properties and poor fluidity of NdFeB magnetic powder, it is necessary to add organic additives such as antioxidants and lubricants, and it is necessary to introduce inert gases such as nitrogen, which will introduce a certain amount of impurity elements such as carbon, nitrogen and oxygen. In the conventional preparation process, impurity elements are very easy to combine with active neodymium-rich, thereby reducing the coercive force of the magnet.

[0004] Based on the above research, a method for preparing NdFeB magnets is needed to solve the contradictory problem of reducing the impurity elements in the magnets while having to introduce impurity elements due to the preparation process. Summary of the invention

[0005] The object of the present invention is to provide a neodymium iron boron magnet and a preparation method and application thereof. The preparation method controls the hydrogen content in the magnet through an incomplete dehydrogenation process, reduces the free energy of the grain boundary phase, avoids the combination of impurity elements and rare earth-rich phases in subsequent processes, thereby reducing the content of impurity elements in the magnet and avoiding the degradation of the magnet performance by impurity elements. At the same time, the preparation method cooperates with a multi-stage sintering process to avoid the problem of cracks forming in the magnet during sintering due to the incomplete dehydrogenation process, and cooperates with a coating process to protect the magnet to avoid the problem of the magnet adsorbing impurities again during subsequent processing.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a neodymium iron boron magnet, the method comprising the following steps:

[0008] S1: preparing NdFeB strips from magnet raw materials, and then subjecting the NdFeB strips to hydrogen cracking treatment to obtain coarse powder;

[0009] The hydrogen cracking treatment includes hydrogen absorption and dehydrogenation steps performed sequentially, and the dehydrogenation temperature is 250-350°C;

[0010] S2: coating the coarse powder in step S1 with an organic additive to obtain a coated material;

[0011] S3: Grinding, molding, sintering and aging the coating material in step S2 to obtain the NdFeB magnet, wherein the sintering treatment includes sintering in at least two temperature stages.

[0012] When the sintered NdFeB magnet needs to obtain a higher remanence, the content of rare earth elements needs to be reduced in the raw material formula, that is, the rare earth content in the magnet is lower than that of the ordinary magnet, so that a high remanence magnet can be obtained. However, the present invention has found that as the remanence of the magnet approaches the limit of NdFeB, the magnet is more sensitive to environmental changes in the manufacturing process of each process, because the magnet does not have an extra rare earth-rich phase to share the consumption of the rare earth-rich phase by carbon, nitrogen and oxygen brought by the environment, which will cause the deterioration of magnetic properties. Therefore, in the preparation process of high remanence magnets, the influence of introduced impurity elements such as carbon, nitrogen and oxygen on the deterioration of magnetic properties is more significant.

[0013] The present invention has found that when the rare earth content is reduced, the proportion of the rare earth-rich phase in the NdFeB magnet will also decrease. Therefore, the rare earth-rich phase content in the NdFeB magnet powder obtained after smelting, hydrogen crushing and grinding is relatively low. The energy generated by the collision of powders during the grinding and pulverizing process will cause nitrogen to react with the rare earth-rich phase to generate rare earth nitrides and consume the rare earth-rich phase. At the same time, the added organic additives such as lubricants and antioxidants will also react with the rare earth-rich phase during sintering due to failure to volatilize in time, thereby deteriorating the magnetic properties. Therefore, how to reduce the content of impurity elements in high remanence magnets is a technical problem to be solved by the present invention.

[0014] In view of the above problems, the present invention first absorbs hydrogen and then dehydrogenates during the hydrogen cracking process, and the dehydrogenation temperature is controlled at a relatively low temperature of 250-350°C to perform incomplete dehydrogenation, limiting the coarse powder to have a certain amount of hydrogen content. The purpose is to control the hydrogen content in the rare earth-rich phase of the coarse powder and reduce the free energy of the grain boundary phase, thereby effectively avoiding the combination of impurity elements and rare earth-rich phases in subsequent processes, reducing the impurity element content in the magnet, and further avoiding the degradation of magnetic properties by impurity elements.

[0015] However, when dehydrogenation is incomplete, a certain amount of hydrogen remains in the coarse powder. If a conventional sintering process is subsequently used, the hydrogen will escape in a short period of time in a high temperature environment, which may easily cause cracks in the sintered magnet. Therefore, in order to further solve the problem of magnet cracking during sintering due to the incomplete dehydrogenation process, the present invention adopts a multi-stage sintering process in at least two temperature stages to allow hydrogen to escape slowly and avoid the generation of cracks in the magnet.

[0016] In addition, although a certain amount of hydrogen is retained in the coarse powder and the energy of the grain boundary phase is relatively low, the coarse powder will still have problems such as adsorbing impurities in subsequent grinding and molding processes, resulting in an increase in the content of impurity elements in the magnet. Therefore, the present invention also coats the coarse powder to form a uniform protective film on the outer surface of the coarse powder to protect the coarse powder.

[0017] The dehydrogenation temperature in step S1 is 250-350°C, for example, it can be 250°C, 270°C, 290°C, 310°C, 330°C or 350°C. Further preferably, the dehydrogenation temperature in step S1 is 290-310°C, for example, it can be 290°C, 292°C, 295°C, 300°C, 305°C or 310°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In order to retain a specific content of hydrogen in the coarse powder, the present invention adopts a specific dehydrogenation temperature, preferably 290-310° C., to ensure that the coarse powder contains an appropriate hydrogen content.

[0019] Preferably, the dehydrogenation time in step S1 is 5 to 60 min, for example, 5 min, 15 min, 25 min, 35 min, 45 min, 55 min or 60 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Preferably, the hydrogen absorption time in step S1 is 40 to 120 min, for example, 40 min, 60 min, 80 min, 100 min or 120 min, and the hydrogen absorption is carried out under a hydrogen pressure of 0.2 to 0.4 MPa, for example, 0.2 MPa, 0.3 MPa or 0.4 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] The present invention can also control the amount of hydrogen absorption by controlling the hydrogen absorption time, thereby controlling the hydrogen content in the coarse powder after dehydrogenation.

[0022] Preferably, the hydrogen content in the coarse powder in step S1 is 1500-2000 ppm, for example, 1500 ppm, 1700 ppm, 1900 ppm or 2000 ppm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the method of coating the organic additive in step S2 comprises a spraying method.

[0024] Preferably, the spraying method comprises cold spraying the organic additive onto the surface of the coarse powder by means of pressurized gas, the gas being defined as argon.

[0025] The coating method described in the present invention is spray coating, which uses high-pressure gas to carry organic additives so that the organic additives are evenly coated on the surface of the coarse powder. Compared with the method of evaporating the organic additives for coating, no additional heating is required to evaporate the organic additives, which reduces production links and improves production efficiency. At the same time, the coarse powder is prevented from contacting the organic additive vapor with a high temperature, further reducing the risk of powder oxidation.

[0026] Preferably, the spray pressure is 0.3-1 MPa, for example, 0.3 MPa, 0.5 MPa, 0.7 MPa, 0.9 MPa or 1 MPa, and the time is 30-90 min, for example, 30 min, 50 min, 70 min or 90 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the spraying is performed while stirring the coarse powder.

[0028] Preferably, the number of carbon atoms of the organic additive is less than 12, for example, it can be 11, 9, 7, 5 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Exemplarily, the organic additive includes any one or at least two or a combination of at least two of petroleum ether, isobutyric acid, pivalic acid amide, pivalic acid, 3-methyl-2-butanone, 2-ethyl-1-butylamine or 2-ethyl-1-butanol.

[0029] Preferably, the sintering treatment in step S3 includes first heating to a first temperature at a first heating rate for heat preservation, then heating to a second temperature at a second heating rate for heat preservation, then heating to a third temperature at a third heating rate for heat preservation, and finally heating to a fourth temperature at a fourth heating rate for heat preservation.

[0030] Preferably, the first heating rate, the second heating rate, the third heating rate and the fourth heating rate decrease in sequence.

[0031] The present invention adopts a multi-stage sintering process and cooperates with a gradually reduced heating rate to control the speed of hydrogen removal during the sintering process, promote the slow escape of hydrogen, and avoid the generation of magnet cracks.

[0032] Preferably, the first heating rate is 2 to 4°C / min, for example, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min or 4°C / min, the first temperature is 300 to 380°C, for example, 300°C, 320°C, 340°C, 360°C or 380°C, and the time for heating to the first temperature and keeping warm is 1 to 2h, for example, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the second heating rate is 2 to 3°C / min, for example, 2°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min or 3°C / min, the second temperature is 550 to 650°C, for example, 550°C, 570°C, 590°C, 610°C, 630°C or 650°C, and the time for heating to the second temperature and keeping warm is 1 to 2h, for example, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the third heating rate is 1.5-2°C / min, for example, it can be 1.5°C / min, 1.7°C / min, 1.9°C / min or 2°C / min, the third temperature is 800-900°C, for example, it can be 800°C, 820°C, 840°C, 860°C, 880°C or 900°C, and the time for heating to the third temperature and keeping warm is 2-3h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] The present invention particularly controls the heating rate and the heat preservation time in the temperature stages of 550-650° C. and 800-900° C., which can further promote the slow escape of hydrogen.

[0036] Preferably, the fourth heating rate is 1-2°C / min, for example, it can be 1°C / min, 1.2°C / min, 1.4°C / min, 1.6°C / min, 1.8°C / min or 2°C / min, the fourth temperature is 1000-1080°C, for example, it can be 1000°C, 1020°C, 1040°C, 1060°C or 1080°C, and the time for heating to the fourth temperature and keeping warm is 3-5h, for example, it can be 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the vacuum degree of the sintering process is 10 ~2 ~10 2 Pa, for example, can be 10 ~2 Pa, 10 ~1 Pa, 10Pa or 10 2 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the preparation of the NdFeB stripping sheet in step S1 includes melting and casting the magnet raw material.

[0039] Preferably, the vacuum degree of the smelting is 10 ~2 ~10 2 Pa, for example, can be 10 ~2 Pa, 10 ~1 Pa, 10Pa or 10 2 Pa, the temperature is 1300-1500°C, for example, it can be 1300°C, 1350°C, 1400°C, 1450°C or 1500°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the casting temperature is 1400-1500°C, for example, 1400°C, 1420°C, 1440°C, 1460°C, 1480°C or 1500°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the thickness of the NdFeB strip in step S1 is 0.2-0.5 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] Preferably, the grinding method in step S3 includes air flow grinding, and the pressure of the air flow grinding is 0.5-0.8 MPa, for example, it can be 0.5 MPa, 0.6 MPa, 0.7 MPa or 0.8 MPa, and the particle size D50 of the particles ground by air flow is 2-4.5 μm, for example, it can be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0043] Preferably, the molding in step S3 includes mixing and pressing the abrasive and a lubricant, wherein the lubricant is 0.1-0.14% by weight of the abrasive, for example, 0.1%, 0.11%, 0.12%, 0.13% or 0.14%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the pressing is performed under a magnetic field, and the magnetic field strength of the magnetic field is 1.8 to 2.5 T, for example, it can be 1.8 T, 2 T, 2.2 T, 2.4 T or 2.5 T, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the aging treatment in step S3 includes firstly performing a primary aging treatment at a temperature of 900-1000° C., such as 900° C., 920° C., 940° C., 960° C., 980° C. or 1000° C. for 1-4 h, such as 1 h, 2 h, 2.5 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h or 4 h, and then performing a secondary aging treatment at a temperature of 500-550° C., such as 500° C., 520° C., 540° C. or 550° C., for 4-10 h, such as 4 h, 5 h, 6 h, 7 h, 7.5 h, 8 h, 9 h or 10 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] In a second aspect, the present invention provides a NdFeB magnet, which is prepared by the preparation method described in the first aspect.

[0047] Preferably, the NdFeB magnet comprises RTBM, wherein R comprises Nd and other rare earth elements other than Nd, the other rare earth elements other than Nd comprise any one of Pr, La, Ce, Dy, Tb or Ho or a combination of at least two thereof, T comprises Fe and impurity elements, B is boron, and M comprises any one of Co, Cu, Ga, Zr, Ti, Nb, Al, Ag or W or a combination of at least two thereof.

[0048] Preferably, in the NdFeB magnet, the content of R is 28-29.5wt% (preferably 28-29wt%), for example, it can be 28wt%, 28.5wt%, 29wt% or 29.5wt%, the content of B is 0.85-1.05wt%, for example, it can be 0.85wt%, 0.9wt%, 0.95wt%, 1wt%, or 1.05wt%, and the content of M is greater than 0wt% and less than or equal to 3wt%, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%. %, T content is the balance, the content of carbon impurity elements is 200-500ppm, for example, it can be 200ppm, 300ppm, 400ppm or 500ppm, the content of oxygen impurity elements is 300-500ppm, for example, it can be 200ppm, 300ppm, 400ppm or 500ppm, the content of nitrogen impurity elements is 50-100ppm, for example, it can be 50ppm, 70ppm, 90ppm or 100ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0049] In a third aspect, the present invention provides an application of the NdFeB magnet as described in the second aspect, wherein the application includes use in the automotive industry, electronic communications, clean energy, industrial robots or aerospace fields.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The present invention adopts an incomplete dehydrogenation process to control the hydrogen content in the powder from the coarse powder preparation stage, reduce the free energy of the grain boundary phase, and reduce the content of impurity elements in the magnet, thereby effectively avoiding the combination of impurity elements and rare earth-rich phases in subsequent processes and avoiding the degradation of magnetic properties by impurity elements. At the same time, in the subsequent preparation process, the present invention cooperates with a multi-stage sintering process on the one hand to avoid the problem of cracks in the magnet caused by the non-dehydrogenation process, and on the other hand, a uniform protective film is formed on the surface of the coarse powder through a coating process to protect the coarse powder. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0053] Example 1

[0054] This embodiment provides a method for preparing a neodymium iron boron magnet, the preparation method comprising the following steps:

[0055] S1: Prepare the magnet raw materials according to Nd 28 Cu 0.15 Co0.5 Ga 0.1 Zr 0.1 B 0.9 Fe 余 The amount of the formula was mixed and then the vacuum degree was 7×10 ~2 The molten steel was melted in a high-frequency vacuum induction melting furnace at 1400°C, and then cast at 1450°C by a rapid solidification process to obtain a strip-spinning sheet with a thickness of 0.28 mm.

[0056] S2: Then the strip is subjected to hydrogen absorption, dehydrogenation and cooling treatment, wherein the hydrogen absorption is carried out under the condition of hydrogen pressure of 0.2MPa, the hydrogen absorption time is 80min, and the dehydrogenation is carried out under the condition of vacuuming and heating, the dehydrogenation temperature is 310°C, and the dehydrogenation time is 30min, to obtain a coarse powder (the hydrogen content in the coarse powder is 1800ppm), and then a spray method is adopted to attach petroleum ether to the surface of the coarse powder by cold spraying with high-pressure argon gas to obtain a coating material, wherein the coarse powder is stirred while spraying, the spraying pressure is 0.5MPa, and the time is 45min;

[0057] S3: Under a nitrogen atmosphere, the coated material is subjected to a jet mill to obtain a grinding material (fine powder) with a powder particle size D50 of 4.0 μm, wherein the pressure of the jet mill grinding chamber is 0.68 MPa;

[0058] S4: Add 0.12% of the weight of the fine powder to the lubricant zinc stearate after air flow milling, and then press it under a magnetic field strength of 1.8T to obtain a density of 4.0g / cm 3 The compact is demagnetized;

[0059] S5: The green compact obtained in step S4 is placed in a vacuum chamber with a degree of vacuum of 8×10 ~2 Pa vacuum induction furnace, slowly heat up to 350℃ at a heating rate of 3.2℃ / min, and keep warm for 1.5h; then slowly heat up to 620℃ at a heating rate of 2.5℃ / min, and keep warm for 1.5h; then slowly heat up to 850℃ at a heating rate of 1.8℃ / min, and keep warm for 2h; finally, slowly heat up to 1050℃ at a heating rate of 1.2℃ / min, and keep warm for 4h;

[0060] S6: After sintering, the aging treatment is performed at 890° C. for 2 h under vacuum conditions, and then the temperature is raised after cooling to room temperature, and a second aging treatment is performed at 510° C. for 6.5 h to obtain the NdFeB magnet.

[0061] Example 2

[0062] This embodiment provides a method for preparing a neodymium iron boron magnet, the preparation method comprising the following steps:

[0063] S1: Prepare the magnet raw materials according to Nd 28 Cu 0.15 Co 0.5 Ga 0.1 Zr 0.1 B 0.9 Fe 余 The formula amount is mixed, and then the vacuum degree is 10 ~2 The molten steel was melted in a high-frequency vacuum induction melting furnace of Pa at a temperature of 1300°C, and then cast at a temperature of 1500°C by a rapid solidification process to obtain a strip-spinning sheet with a thickness of 0.5 mm.

[0064] S2: Then the strip is subjected to hydrogen absorption, dehydrogenation and cooling treatment, wherein the hydrogen absorption is carried out under the condition of a hydrogen pressure of 0.5 MPa, the hydrogen absorption time is 40 min, and the dehydrogenation is carried out under the condition of vacuuming and heating, the dehydrogenation temperature is 290° C., and the dehydrogenation time is 60 min, to obtain a coarse powder (the hydrogen content in the coarse powder is 1500 ppm), and then a spraying method is adopted to attach petroleum ether to the surface of the coarse powder by cold spraying with high-pressure argon gas to obtain a coating material, wherein the spraying is carried out while stirring the coarse powder, the spraying pressure is 0.3 MPa, and the time is 90 min;

[0065] S3: Under a nitrogen atmosphere, the coated material is subjected to a jet mill to obtain a grinding material (fine powder) with a powder particle size D50 of 2 μm, wherein the pressure of the jet mill grinding chamber is 0.8 MPa;

[0066] S4: Add 0.1% of the weight of the fine powder to the lubricant zinc stearate after air flow milling, and then press it under a magnetic field strength of 2.5T to obtain a density of 4.0g / cm 3 The compact is demagnetized;

[0067] S5: slowly heating the green compact obtained in step S4 to 380°C at a heating rate of 2.5°C / min in a vacuum induction furnace with a vacuum degree of 1Pa, and keeping the temperature for 1h; then slowly heating the green compact to 550°C at a heating rate of 2°C / min, and keeping the temperature for 2h; then slowly heating the green compact to 900°C at a heating rate of 1.5°C / min, and keeping the temperature for 2h; finally slowly heating the green compact to 1080°C at a heating rate of 1°C / min, and keeping the temperature for 3h;

[0068] S6: After sintering, the aging treatment is performed at 1000° C. for 3 hours under vacuum conditions, and then the temperature is raised after cooling to room temperature, and a second aging treatment is performed at 500° C. for 5 hours to obtain the NdFeB magnet.

[0069] Example 3

[0070] This embodiment provides a method for preparing a NdFeB magnet. The preparation method is the same as that of Embodiment 1 except that the dehydrogenation temperature in step S2 is 350° C. so that the hydrogen content in the coarse powder can be adaptively changed.

[0071] Example 4

[0072] This embodiment provides a method for preparing a NdFeB magnet. The preparation method is the same as that of Embodiment 1 except that the dehydrogenation temperature in step S2 is 250° C. so that the hydrogen content in the coarse powder can be adaptively changed.

[0073] Example 5

[0074] This embodiment provides a method for preparing a NdFeB magnet. The preparation method is the same as that of Embodiment 1 except that the heating rate in step S5 is 3.2° C. / min.

[0075] Comparative Example 1

[0076] This comparative example provides a method for preparing a NdFeB magnet. The method is the same as Example 1 except that the dehydrogenation temperature in step S2 is 450° C. to adapt the hydrogen content in the coarse powder.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a NdFeB magnet. The method is the same as Example 1 except that the dehydrogenation temperature in step S2 is 560° C. to adapt the hydrogen content in the coarse powder.

[0079] Comparative Example 3

[0080] This comparative example provides a method for preparing a NdFeB magnet. The preparation method is the same as Example 1 except that dehydrogenation is not performed in step S2.

[0081] Comparative Example 4

[0082] This comparative example provides a method for preparing a NdFeB magnet. The preparation method is the same as that of Example 1, except that the coarse powder obtained in step S2 is not subjected to spray coating treatment.

[0083] Comparative Example 5

[0084] This comparative example provides a method for preparing a NdFeB magnet. The method includes step S5 in which the vacuum degree is 10 ~2 ~10 2 The method is the same as that of Example 1 except that the sintering is carried out in a vacuum induction furnace of 1000 Pa at 1050° C. for 8 h and then slowly air-cooled.

[0085] The magnetic properties of the NdFeB magnets obtained in the above embodiments and comparative examples were tested using a BH plotter, and the test results are shown in Table 1. At the same time, the contents of C, N and O in the NdFeB magnets obtained in the above embodiments and comparative examples are shown in Table 1:

[0086] Table 1

[0087]

[0088] From the above table we can see that:

[0089] (1) It can be seen from Example 1 and Comparative Examples 1-3 that if the dehydrogenation temperature is too high, it is impossible to ensure that the coarse powder contains a reasonable hydrogen content. If the dehydrogenation step is not performed, the hydrogen content in the coarse powder is also unreasonable. Therefore, the performance of the magnet cannot be guaranteed. The present invention can regulate the hydrogen content in the coarse powder through a dehydrogenation step at a specific temperature, reduce the impurity elements in the magnet, and further reduce the degradation of the magnetic properties by the impurity elements; it can be seen from Example 1 and Comparative Example 4 that the coating step of the present invention can form a uniform protective film on the surface of the coarse powder, further reduce the impurity content in the magnet, and improve the magnetic properties of the magnet; it can be seen from Example 1 and Comparative Example 5 that the present invention adopts a multi-stage sintering process to promote the slow escape of hydrogen during the sintering process, avoid cracking of the magnet, and ensure the performance of the magnet.

[0090] (2) It can be seen from Examples 1 and 3-4 that the preferred dehydrogenation temperature of the present invention is within a specific range of 290-310°C to ensure that the hydrogen content in the coarse powder is within a more reasonable range, so that it can better cooperate with subsequent sintering and other processes to further improve the performance of the magnet; It can be seen from Examples 1 and 5 that the multi-stage sintering process of the present invention, combined with a gradually reduced sintering heating rate, can further allow hydrogen to escape slowly, reduce the probability of cracks in the blank, and improve the performance of the magnet.

[0091] In summary, the present invention provides a neodymium iron boron magnet and a preparation method and application thereof. The preparation method controls the hydrogen content in the magnet through an incomplete dehydrogenation process, reduces the content of impurity elements in the magnet, and avoids the degradation of the magnet performance by impurity elements. At the same time, the preparation method cooperates with a multi-stage sintering process to avoid the problem of cracks forming in the magnet during sintering due to the incomplete dehydrogenation process, and cooperates with a coating process to protect the magnet to avoid the problem of the magnet adsorbing impurities again during subsequent processing.

[0092] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a neodymium iron boron magnet, characterized in that: The preparation method comprises the following steps: S1: preparing NdFeB strips from magnet raw materials, and then subjecting the NdFeB strips to hydrogen cracking treatment to obtain coarse powder; The hydrogen cracking treatment includes hydrogen absorption and dehydrogenation steps performed sequentially, and the dehydrogenation temperature is 250-350°C; S2: coating the coarse powder in step S1 with an organic additive to obtain a coated material; S3: Grinding, molding, sintering and aging the coating material in step S2 to obtain the NdFeB magnet, wherein the sintering process is performed in at least two temperature stages.

2. The preparation method according to claim 1, characterized in that: The dehydrogenation temperature in step S1 is 290-310°C; And / or, the dehydrogenation time in step S1 is 5 to 60 minutes; And / or, the hydrogen absorption time in step S1 is 40 to 120 minutes, and the hydrogen absorption is carried out under a hydrogen pressure of 0.2 to 0.4 MPa; And / or, the coarse powder in step S1 has a hydrogen content of 1500-2000 ppm.

3. The preparation method according to claim 1 or 2, characterized in that: The method of coating the organic additive in step S2 comprises a spraying method; and / or, when coating the organic additive in step S2, the organic additive is cold-sprayed on the surface of the coarse powder by pressurized gas; And / or, when coating the organic additive in step S2, the spray pressure used is 0.3-1 MPa and the time is 30-90 min; And / or, when coating the organic additive in step S2, the carbon number of the organic additive used is less than 12.

4. The preparation method according to claim 1 or 2, characterized in that: The sintering treatment in step S3 includes first heating the temperature to a first temperature at a first heating rate and then keeping the temperature, then heating the temperature to a second temperature at a second heating rate and then keeping the temperature, then heating the temperature to a third temperature at a third heating rate and then keeping the temperature, and finally heating the temperature to a fourth temperature at a fourth heating rate and then keeping the temperature; And / or, during the sintering process in step S3, the first heating rate, the second heating rate, the third heating rate and the fourth heating rate decrease in sequence.

5. The preparation method according to claim 4, characterized in that: The first heating rate is 2-4°C / min, the first temperature is 300-380°C, and the time for heating to the first temperature and keeping warm is 1-2h; And / or, the second heating rate is 2-3°C / min, the second temperature is 550-650°C, and the time for heating to the second temperature and keeping warm is 1-2h; And / or, the third heating rate is 1.5-2°C / min, the third temperature is 800-900°C, and the time for heating to the third temperature and keeping warm is 2-3h; And / or, the fourth heating rate is 1-2°C / min, the fourth temperature is 1000-1080°C, and the time for heating to the fourth temperature and keeping warm is 3-5h; And / or, the vacuum degree of the sintering process is 10 ~2 ~10 2 Pa.

6. The preparation method according to claim 1 or 2, characterized in that: The step S1 of preparing the NdFeB stripping sheet includes smelting and casting the magnet raw material; And / or, when preparing the NdFeB stripping sheet in step S1, the vacuum degree of melting is 10 ~2 ~10 2 Pa, temperature is 1300~1500℃; And / or, when preparing the NdFeB strip sheet in step S1, the casting temperature is 1400-1500°C; And / or, the thickness of the NdFeB strip in step S1 is 0.2-0.5 mm.

7. The preparation method according to claim 1 or 2, characterized in that: The grinding method in step S3 includes airflow grinding, the pressure of the airflow grinding is 0.5-0.8 MPa, and the airflow grinding is performed until the particle size D50 of the particles is 2-4.5 μm; And / or, the molding in step S3 includes mixing and pressing the abrasive and a lubricant, wherein the lubricant is 0.1 to 0.14% by weight of the abrasive; And / or, during the molding in step S3, the pressing is performed under a magnetic field, and the magnetic field strength of the magnetic field is 1.8 to 2.5 T; And / or, the aging treatment in step S3 includes firstly performing a primary aging treatment at a temperature of 900-1000° C. for 1-4 hours, and then performing a secondary aging treatment at a temperature of 500-550° C. for 4-10 hours.

8. A neodymium iron boron magnet, characterized in that: The NdFeB magnet is prepared by the preparation method according to any one of claims 1 to 7.

9. The NdFeB magnet according to claim 8, characterized in that: The NdFeB magnet comprises RTBM, wherein R comprises Nd and other rare earth elements other than Nd, the other rare earth elements other than Nd comprise any one of Pr, La, Ce, Dy, Tb or Ho or a combination of at least two thereof, T comprises Fe and an impurity element, B is boron, and M comprises any one of Co, Cu, Ga, Zr, Ti, Nb, Al, Ag or W or a combination of at least two thereof; And / or, in the NdFeB magnet, the content of R is 28-29.5wt%, the content of B is 0.85-1.05wt%, the content of M is greater than 0wt% and less than or equal to 3wt%, the content of T is the remainder, the content of carbon impurity elements is 200-500ppm, the content of oxygen impurity elements is 300-500ppm, and the content of nitrogen impurity elements is 50-100ppm.

10. Use of the NdFeB magnet as claimed in claim 8 or 9, characterized in that: The applications include use in the automotive industry, electronic communications, clean energy, industrial robots or aerospace.

Citation Information

Cited By

  • Large-size neodymium-iron-boron magnet and preparation method thereof

    CN120164717A

  • Large-size neodymium-iron-boron magnet and method for producing same

    CN120164717B